Utilisation of Industrial, Agricultural and Forest Waste - Jain, N. C.; Gupta, R. C. (Indian Forester, 1968)
Enormous quantities. of wastes (industrial, agricultural, and forests) are available in the country. Their proper utilisation is important for the balanced economy of the country. In this note utilisation of some of these has been sought in the field of plywood (adhesives, fillers and extenders, etc.) and building boards (fibre board, particle board and plastic boards). A gel obtained from paddy husk has given good results when tried as extender in U.F. glue and P.F. glue for making plywood. It appears possible that the entire wheat flour now being used in the Industry could be replaced by this gel. In the field of building boards, rubber wood has given encouraging results. Ground Nut Shell, yet another agricultural waste has yielded encouraging particle boards.